Chromium Adsorptive Removal From Industrial Wastewater Using Various Reactive Media- A Mini Review - Mokokwe, Gobusaone; Mpodi, Emmanuel Karabo; Makoi, Topoyame Isaac (International Journal of Sciences: Basic and Applied Research (IJSBAR), 2021)
Effluents from industries frequently contain a variety of chromium ions such as hexavalent chromium and trivalent chromium which can adversely pose threats to terrestrial and aquatic life. Hexavalent chromium is more toxic than trivalent chromium thus needs to be removed from effluents. Adsorption is a water and wastewater treatment technology which plays a significant role in the removal of heavy metals including chromium from effluents. In this review paper, the performance of distinct inexpensive reactive bio adsorbents and other adsorbents used by different researchers was reviewed. The findings from different studies indicated that most of the adsorbents for the removal of chromium are technically uncomplicated and mostly had outstanding performance. Factors frequently and seldom used for selection of best media for adsorption were also reviewed. Although many researchers have proven that most of the media have outstanding performance, there is still paucity of information on the effects of practical issues such as mechanical strength of media, its toxicity and leachability, abrasion on adsorption capacity. Findings also shown that sodium hydroxide is the best regeneration eluent. The findings of different studies in this review have demonstrated that different low-cost bio adsorbents can be employed in industrial wastewater treatment processes to remove chromium.